Correlations between Distribution of Producer Services and Urban Built Environment in Metro Station Areas: A Case of Xi’an, China - Qi Zhang; Yu-Jie Zhang; Xin Ding; Qiu-Ping Wang (Advances in Civil Engineering)
Since impacts of rail transit on urban industries and space most obviously appear in metro station areas, correlations between the spatial distribution of producer services and urban built environment in metro station areas are studied in Xi’an, China. At first, the scope determining methods of a metro station area were separately proposed for both single-line station and multiline transfer station based on their construction and transportation modes. Then, when the producer services were divided into 6 categories of business, POI numbers of enterprises of each category in metro station areas were collected and weighted to calculate the distribution intensity for categories. Finally, on condition that the urban built environment of a metro station area included job and residence space, outdoor activity space, and municipal road space, correlation performances between the distribution intensity of categories and indexes representing 3 space elements of the built environment were calculated through second-order partial correlation analysis, while the corresponding mechanisms of correlations were explained too. The main conclusions of this paper indicate that there are significant positive correlations between the distribution intensity and the diversity index of job and residence space for most categories, whereas significant negative correlations between it and the openness index of outdoor activity space for most categories. Moreover, positive but weak correlations were appeared between the distribution intensity and the street network density index of municipal road space only for categories of intermediary consulting and leasing.